PENGELOLAAN TAMAN NASIONAL UJUNG KULON (TNUK) - Abdurrachman, Abdurrachman; Pratiwi, Annisa (Journal of Indonesian Tourism and Policy Studies, 2017)
This study aims to explain how the management of Ujung Kulon National Park (TNUK). Data obtained by interview, observation during the Job Training, and literature study. The result of this research is the effort of management of Ujung Kulon National Park (TNUK).